Digital Consumerism among Nepalese College Students: A Study of Online Shopping Behavior - Manandhar, Raju Bhai (Tribhuvan University Journal, 2023)
Online shopping is a form of electronic commerce that allows consumers to purchase products or services directly from sellers over the Internet using a web browser. The main objective of this study is to explore the relationship between price, convenience, security, and online shopping behavior of students in Kathmandu. The research adopted the analytical research design. Four hundred students from different colleges in Kathmandu Valley were selected for this study. The convenience sampling method was used while selecting the respondents. The questionnaire survey was developed to collect primary data. The study adopted cross tab, independent t-test, and correlation to analyze the data. Convenience is the most preferable factor when selecting a product in online shopping. Price, convenience, and security are positively correlated with online shopping behavior. As per the result, the price highly correlates with online shopping behavior. Hence, online shopping companies must maintain the product’s standard price to meet consumers’ expectations. Online shopping companies also consider improving websites with solid security mechanisms for the convenience of online shopping to build up the company’s image. Likewise, the firm should consider the preferable factors of online shopping for a better budget allocation for promoting their online business. Future researchers can study the online shopping behavior of the general public with a larger sample size.